International Journal of Computer Processing of Languages - World Scientific (Firm) (Singapore ; Hong Kong : World Scientific, 2000)
Access available from 2003-
Keywords: Chinese language -- Data processing -- Periodicals; Oriental languages -- Data processing -- Periodicals; Chinese characters -- Data processing -- Periodicals; Information storage and retrieval systems -- Chinese language -- Periodicals; Information storage and retrieval systems -- Chinese characters -- Periodicals